The Effect of garlic on serum cholesterol level in rats fed on high fat diets - Mohd Shaun Farleen Sahabuddin.
Garlic has been reported to possess the effect of lowering serum cholesterol level in blood thus may reduced the occurrence of cardiovascular disease but lacking scientific reports available reported. Twenty four Sprague Dawley rats of sixteen weeks old were purchased for this study and they were divided into four groups (n = 6). Hypercholesterolemia was induced by feeding twenty percent of butter as high fat diet for two weeks and the treatment diet for three weeks. Group A was fed on normal diet, group B was fed on normal diet + butter, group C was fed on normal diet + butter + garlic and group D was fed on normal diet + butter + dexamethasone. The plasma serum cholesterol, average body weight and organ weight were determined along five weeks of study. From this study, the results showed significant decreased in the serum total cholesterol level for group C and group D (p<0.05). The average body weight was significantly different between the initial body weight and final body weight. The organ weight showed significant decreased in mean blotted dry liver weight (p[<0.05) in group C and group D. These observations indicate that consumption of raw garlic has beneficial effect in lowering serum total cholesterol level and promote weight control.